Comparison of Basic Science Process Skills for Students on Electrical Materials with the Rasch Model Analysis - Sri Lestari Handayani (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2021)
Prospective teacher students must have good science process skills to create learning that focuses on science process skills-based learning. This study aims to describe the comparison of the basic science process skills of prospective elementary school teachers in electric subjects. This research is descriptive. The sample of this study was 184 students consisting of 104 students in the 4th semester and 80 students in the 6th semester. The data collection technique was using a test that consists of 25 questions about basic science process skills. Data analysis using the Wright Person Map in Rasch Model. Based on the results, the researcher obtained information that most prospective elementary teachers' science process skills were classified as moderate. In addition, the results were obtained that the science process skills of 6th-semester students were better than the 4th semester. This research also found that the science process skill of female students was better than male students.